An evaluative study on the role of the Philippine Library Materials Project Foundation, Inc. in the collection development of selected academic libraries - Samson, Ma. Cristina B.; Faderon, Rosalie B.; Picache, Ursula G. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1995)
This study was conducted to examine and evaluate the impact of the Philippine Library Materials Project Foundation, Inc. (PLMP) in forty-five academic libraries with regards to their collection development programs. PLMP is a cooperative non-profit organization which collects materials abroad to help expand the resources of Philippine libraries.
Specifically, the study sought to find out the effectiveness of PLMP in helping member libraries build/develop their library collections and the usefulness and relevance of the library materials they bring into the country. Using the descriptive survey approach, questionnaires and interviews were used in gathering the desired information. Among the findings of the study are: 1. Majority of the members/subscribers of PLMP come from the provinces. 2. Library materials acquired from PLMP are old but useful and relevant to the various curricular programs and the Philippine educational system. 3. Generally PLMP's objectives are being met and fulfilled. 4. The operations and management of PLMP were rated efficient by member libraries. 5. Overall, the project has been effective in bringing into the country useful and relevant library materials and in helping member libraries build/develop their library collections.
A very significant observation of the study is the positive impact of PLMP on member libraries. To ensure the effectiveness of the project, it is recommended that an evaluation/assessment be conducted at least every ten years.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: Academic libraries -- Collection development -- Philippines -- Manila Metropolitan Area